The Frataraka of Persis - Raúl Navas-Moreno (Karanos)
This article aims to survey the sources on the Frataraka to examine their historical role. Initially, we will provide a concise overview of the academic community's contributions and the status quaestionis, presenting the primary testimonies available regarding the Frataraka dynasts and will elucidate the varied topics associated with dubious issues. Furthermore, the article will endeavour to connect the dynasts with their socio-cultural and historical context to establish an inclusive interpretation that significantly highlights the closely linked political entities of the Frataraka and Seleucids, together with their connections to Achaemenids, Arsacids, and Sasanians.